Elaboration of analysis of mental health situation (ASIS) in the city of Huánuco - Suero Rojas, Enrique (2009)
The study was conducted with the purpose of conducting an analysis of the situation of the mental health, through the most frequent casuistry determination in conditions of the region Huánuco. Therefore it was taken a sample that included patients of supporting hospital, ESSALUD, Hermilio Valdizán Hospital and Carlos Showing Ferrari hospital. Results standing out that the majority belong to female patients reaching values of 70% and according to the casuistry, the most common diagnoses are: widespread anxiety disorder (21.2%), adaptation disorders (15.1%); and mixedanxiety-depressive disorder (10.7%). A 37.72% presents a diagnosis of Anxiety Disorders, Depressive Episodes 8%, and 60.83% are disorders related to the emotions. In regarding of associated factors, we see that, 65% of them belong to socioeconomic level C. 26% at the Level D, and 15% belongs at the level B. According the type of family, 53% are dysfunctional type, 31% Functional type and 16% single-parent. The grade of paternal instruction is in its majority (18%) of Primary and Secondary completed; parents with incomplete primary are 14% and 13% are illiterate, one of the most significant occurrences is that total of patients nobody has studies of Post Grade. The majority of the patients (97 %) has not been a victim of political violence; (90 %) does not present signs of alcoholism; (61) are not victims of familiar violence; (44 %) it presents Locus of external control; (63 %) indicates to have received sexual education; (70%) of patients say that know the roll of the psychologist; (91%) indicates no have any relative who presents a psychopathology.